Relationships between leaf trichome characteristics and field resistance to cassava green mite (Mononychellus tanajoa (Bondar) - Nukenine, E.N.; Dixon, Alfred G.O.; Hassan, A.T.; Zalom, F.G. (Systematic and Applied Acarology Society, 2002)
Experiments were conducted at Ibadan, Nigeria to assess the effect of leaf trichome characteristics (pubescence intensity index, length, and orientation) on field resistance of cassava to the green spider mite, Mononychellus tanajoa (Bondar). There were significant (P < 0.01) differences in M. tanajoa density, damage score and leaf trichome characteristics among the cultivars. During the dry season (February, 1993 and 1994) and the early part of the rainy season (May, 1993), there were significant (P < 0.01) negative correlations between pubescence intensity index on the top leaves (leaf 3) and mite damage. Significant negative correlations were also obtained between trichome length and damage in the dry season (February, 1993) (P < 0.05), and between trichome orientation and mite damage in the rainy season (May, 1993) (P < 0.01). Correlation between pubescence intensity index and mite density on the top leaves was significant and positive only in the "middle" of the rainy season (August, 1993). A significant (P < 0.01) negative correlation was obtained between trichome orientation and mite density in the dry season (February, 1993). The results suggest that, during the dry season, a high pubescence intensity significantly reduces leaf damage by M. tanajoa through mechanical disturbance of movement and feeding. Trichome length is more important than trichome orientation in cassava resistance to M. tanajoa.